Implementasi Model Pembelajaran PJBL Berbantuan Aplikasi Wattpad dalam Meningkatkan Kemampuan Menulis Cerpen Pada Peserta Didik Kelas 5 SD - Parawangsa, Arya; Sahilah, Nadia; Ismelda, Reza; Supriyadi, Supriyadi; Hermawan, Jody Setya (Universitas Pahlawan Tuanku Tambusai, 2024)
Indonesian students' literacy skills are at an alarming level. Based on the results of the 2022 PISA survey, Indonesia is ranked 71st out of 81 countries which shows the low reading and writing abilities of students. Considering that reading and writing skills are interrelated, one way to improve literacy skills is to provide interesting reading material. To achieve this goal, the Project Based Learning (PjBL) learning model can be used, where students are asked to produce products in the form of creative and interesting reading materials. One media that can support this process is the Wattpad application. Wattpad is a digital writing platform used by more than 100 million users worldwide. This application makes it easier for students to express their ideas, thoughts and imaginations in written form. Through Wattpad, students can not only publish their work, but also get direct feedback from readers. This feedback allows students to develop their writing skills in a more efficient and consistent manner. Using Wattpad in project-based learning provides opportunities for students to improve their writing skills, while fostering interest in reading through interactive experiences. Thus, it is hoped that the Wattpad application can be an effective means of increasing the literacy of Indonesian students with an approach that is appropriate to technological developments and learning needs in the digital era.